An Analysis of Rear-End Impact Crash Characteristics and Injury Pattern in Malaysia - Widia, M.; Jamaludin, B.S.; Ab Rashid, A.A.; Sukadarin, E.H.; Fauzan, N.S.; Aziz, H.A.; Osman, H.; Roslin, E.N.; Yassierli; Zadry, H.R.; Prasetyo, Y.T.; Neubert, M.S. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Rear-end crashes are one of the most common types of accidents. The characteristics of rear impact crash (based on accident data in Malaysia) have not been well studied. The objective of this study is to investigate the rear impact crash characteristics in Malaysia between 2016 and 2018 using data obtained from Bukit Aman Traffic Investigation and Enforcement (JSPT), Royal Malaysia Police (RMP) Pol 27. The analysis revealed that motorcycles (40.3%) were the largest contributor to rear-end crashes, followed by occupant car (36.3%), lorry (16.3%), four-wheel (3.8%), bus (1.6%) and other vehicles (1.6%). The majority did not suffer any injury (60.8%), while there were fatalities (16.8%), injuries (14.3%), and severe injuries (8.1%). The highest percentage of fatal crashes occurred at the speed limit area 110 km/h (23.6%). The chi-square test showed that speed limit and type of crash were significantly associated (p<0.01). The result also showed a significant association between main vehicle part damage and injury level (p<0.01). The study shows a thorough examination and analysis of rear impact crash characteristics can provide important and useful information to guide transport policy, vehicle design, and driver education. Further research is needed to fully understand the key factors that contribute to rear-end impact crashes in Malaysia.